Glencoe and the Indians : a real-life family saga which spans two continents, several centuries and more than thirty generations to link Scotland's clans with the native peoples of the American West /: a real-life family saga which spans two continents, several centuries and more than thirty generations to link Scotland's clans with the native peoples of the American West. (2011) - Unknown
No abstract available